Peran Pengungkapan Corporate Social Responsibility dalam Meningkatkan Pengaruh Return on Equity terhadap Nilai Perusahaan - Istikhoroh, Siti; Suhardiyah, Martha (Majalah Ekonomi, 2016)
Abstract The purpose of this study is to analyze the role of Corporate Social Responsibility (CSR) disclosure in improving Return on Equity (ROE) effect on company value on real estate and property companies that go public. The sample is 38 real estate and property companies listed on the Indonesia Stock Exchange (IDX) in the period 2013-2015, which was chosen by purposive sampling. The study was conducted using moderated regresion analysis technique. Based on the test results it can be concluded that ROE has effect on the company value and CSR disclosure can increase the ROE effect on company value. Keywords: Return on Equity, CSR disclosure, Company Values